Effect of achievement-related gamification on brand attachment. Issue 1 (17th November 2021) - Yang, Congcong; Yang, Pianpian; Feng, Yuanyue
Abstract : Purpose: This research draws on self-determination theory and self-construal theory to investigate the effects of achievement-related gamification features on customers' brand attachment in online brand communities. Design/methodology/approach: Survey data ( N  = 523) were collected from customers of typical gamified online brand communities. The research model was examined with structural equation modeling using SmartPLS 3.2. Findings: Achievement-related gamification features positively affect customers' brand attachment via the intrinsic motives of autonomy, competence and relatedness, but not extrinsic motives. Relatedness motive exerts the strongest mediating effect between achievement-related gamification features and brand attachment, followed by competence and autonomy. Moreover, interdependent self-construal positively moderates the effects of achievement-related gamification features on intrinsic (autonomy, competence and relatedness) and extrinsic motives. Originality/value: Theoretically, this study contributes to the brand marketing literature by identifying gamification as a new antecedent for brand attachment. It also contributes to the gamification literature by demonstrating that achievement-related gamification features strengthen brand attachment via intrinsic motives but not extrinsic motives in the specific context of the online brand community. Meanwhile, the relatedness motive exerts the strongest mediating effect between achievement-related gamification features and brand attachment, followed by competence and autonomy. Moreover, this research provides the first empirical evidence that interdependent self-construal moderates the effects of achievement-related gamification features on intrinsic and extrinsic motives. Practically, managers can learn from the results that achievement-related gamification features should be designed to foster customers' intrinsic motives and brand attachment, especially those high in interdependent self-construal levels.